2022
DOI: 10.1155/2022/5685178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe2+ and Fe3+ on the Performance and Microbial Community Composition of a MFC Inoculated with Sulfate-Reducing Sludge and Acetate as Electron Donor

Abstract: A sulfidogenic sludge supplemented with acetate was evaluated in the anodic chamber of microbial fuel cells (MFCs) in the presence of sulfate (SO4-2)/Fe3+ and sulfate (SO4-2)/Fe2+ to investigate the MFC performance and the effect of the iron ions on the composition of the microbial community since sulfate and iron ions are frequently present in wastewater derived from several anthropogenic activities. The current densities were up to 0.025 mA/cm2 and 0.017 mA/cm2 for MFCs with Fe2+ and Fe3+, respectively. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Microorganisms instead utilize Fe 2+ and sulfur for metabolic processes, leading to the formation of Fe 3+ and sulfate ions. This metabolic activity results in a higher concentration of these ions subsequently intensifying the dissolution of sulfide minerals and augmenting the volume of acidic water (González-Paz et al, 2022). A quintessential illustration of this bioleaching phenomenon is the process involving chalcopyrite (CuFeS 2 ) microbial-mediated dissolution (Eq.…”
Section: -mentioning
confidence: 99%
“…Microorganisms instead utilize Fe 2+ and sulfur for metabolic processes, leading to the formation of Fe 3+ and sulfate ions. This metabolic activity results in a higher concentration of these ions subsequently intensifying the dissolution of sulfide minerals and augmenting the volume of acidic water (González-Paz et al, 2022). A quintessential illustration of this bioleaching phenomenon is the process involving chalcopyrite (CuFeS 2 ) microbial-mediated dissolution (Eq.…”
Section: -mentioning
confidence: 99%
“…AKYG1722, known for utilizing SO4 2 ⁻ in N-depleted environments, was notably more abundant under MS treatments 43 . The presence of Herminiimonas, Cyclobacteriaceae, Rhodospirillales, and Gemmatimonadaceae, which can utilize both NO3⁻ and SO4 2 ⁻, indicates a complex interplay within the microbial ecosystem [44][45][46][47] .…”
Section: Soil Microbial Community and Functional Characterizationmentioning
confidence: 99%
“…Hence, various technologies have been investigated, for instance, water electrolysis, biomass gasification, and biological hydrogen production, to achieve more sustainable hydrogen production (Noori et al 2024a). Among them, the process of using renewable electricity for water electrolysis is considered a promising technology (Godula-Jopek 2015). However, precious metal catalysts such as platinum and iridium are often required to be used on the electrodes, which potentially can increase the fabrication cost of the electrolyzers (Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, FexMnOy complexes provided a highly active surface area for the microbes to colonize the carbon cloth (CC) cathode in an MES for CO2 reduction into volatile fatty acids (VFAs), and the improved cathodic current response was about 1.2 times higher than the value using pristine CC cathode (Tabish Noori and Min 2019). While the precise mechanism of iron-based catalytic enhancement in the biocathode remains unclear, it can be postulated that iron facilitates direct extracellular electron transfer, owing to its dual redox states (Fe 2+ /Fe 3+ ) like those observed in microbial c-type cytochromes (González-Paz et al 2022). In an earlier study, the FeS nanosheet demonstrated high catalytic activity and fast electron transfer in abiotic HER with a significantly lower overpotential loss of 142 mV, owing to their intrinsic electron-transferring properties (Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 99%